Exploration of EDM assisted CNT in micro machining using statistical approach - Al Hazza, Muataz Hazza Faizi; Khan, Ahsan Ali; Ali , Mohammad Yeakub (The Institute of Electrical and Electronics Engineers, Inc., 2016)
With the increasing global demand of micro components, the manufacturing technique goes toward miniaturization T. One off these applications is the The carbon nanotube (CNT). It is one of the new applications that that can play vital role in based on economic factors such as material removing rate MRR and the electrode wear rate EWR. The main objective of this research is to explore of EDM assisted CNT for micro machining in terms of economic issue. A set of experiments have been conducted to analyses statically the effect of peak current and CNT concentration on the MRR and EWR. The scatter matrix has been used to analyses the results. Finally anew model has been developed to estimate and predict the output rate between the MRR and EWR.